Uncertain hazards : environmental activists and scientific proof - Tesh, Sylvia Noble, 1937- (Cornell University Press, 2000)
"Ordinary citizens frequently organize around environmental issues on which little scientific evidence exists to back activists' claims. Should we then dismiss such claims as spurious? Or should we side with citizens against the polluters?"